ΠΙΘΟΣ from the Archaeological Museum in Split (Archaeologia Adriatica, 2008)
A fragment of a Greek pithos is published in the article, which was most probably found in central Dalmatia. It is particularly interesting in terms of the graffiti, the numerical symbols ΔΔΔ Π ΙΙΙ, and the decoration of grapevines on the exterior lateral side of the rim. On the basis of the dimensions, the author considers that the pithos had a globular shape (ca. 160 x 150 cm), with a capacity of over 1000 liters, and that it served to store wine in some public area. Although its site of discovery is unknown, the author suggests that it would have been made in one of the well-known production centers: Pharos, Issa, Resnik, and that the form represents a predecessor to the later Roman doliae in this region.The numerical symbol ΔΔΔ Π ΙΙΙ (= 38) is debatable, but it probably represents the price of the pithos itself, given that the process of production of such large vessels was complicated, lengthy, and expensive.
Keywords: Greek pithos; graphite; decoration; capacity; production; price